Development of a novel knowledge-based decision support system for accident prevention of oil and gas drilling process - Mujtaba Asad, Muhammad (2018)
Oil and gas drilling process is highly associated with numerous hazardous conditions and potential risks at onshore and offshore drilling domains due to the unpredictable nature of this procedure. Thus, there is a sheer need of an efficient Knowledge-Based Decision Support System (KBDSS) based on the most effective and innovative potential hazards controlling factors, strategies and preventive measures to overcome the accidents at drilling sites. Therefore, in this study the most hazardous drilling operations with their associated potential hazards and effective hazard controlling factors at Malaysian, Saudi Arabian and Pakistani onshore and offshore drilling industries have been identified. Moreover, based on the identified hazard controls, a new KBDSS has been developed by using MySQL and Visual Studio 2015 software. In this study, sequential explanatory and evaluation research designs have been adopted. The developed system has been implemented on targeted industries to assess its decision-making potential, effectiveness of hazard controls, level of user satisfaction and performance for vestibule safety training activities. The quantitative and qualitative data has been gathered from oil and gas drilling crew (240 respondents) and safety and health experts (9 respondents) through survey instruments and semi-structured interviews. Furthermore, the descriptive and inferential statistical tests have been used for quantitative data analysis. Whereas, “What-If Analysis” and thematic analysis approaches have been utilized for analyzing the qualitative data. According to the overall quantitative and qualitative results of this study, the developed KBDSS based on the identified effective hazard controlling factors and preventive measures, proved to be suitable for appropriate decision making during hazardous conditions as well as for vestibule training activities at both drilling domains at oil and gas industries in Malaysia, Saudi Arabia and Pakistan with in moderate (Mean = 2.50-3.49) and high (Mean = 3.50-5.0) level of mean range. In conclusion, this study has introduced a new and efficient KBDSS for accident prevention at oil and gas extraction process which covers all onshore and offshore drilling operations from different regions to achieve the latest trend of industrial IoT as per international safety standards and regulations.